Evaluación de la relación entre las actividades en las lubricadoras del cantón Bolívar y la carga contaminante que disponen al ambiente - Loor Bermeo, Martha Johana (2013)
The purpose of this research was developed with the aim of establishing the relationship with the activities that generate the operation of washing facilities and services lubricadoras (M. Va, Schettino and quick and shiny) in the city of sock, giving compliance with environmental regulations of Ecuador, through the completion of environmental Assessment and minimization opportunity. To this end we determined the area of influence by recognizing the activities and potential environmental effects of such practices exist, taking into account the characteristics of the establishments in the middle and its activities, operations, services in these centers technical visits were conducted and the analysis of the pollution load in each of the washers and lubricadoras, were analyzed in parallel running activities during the process of washing and car lubricated. The environmental assessment and minimization opportunity that generally determine the relationship would have the environment activities in service establishments. Based on the identified impacts was designed environmental action plan for the prevention and reduction of pollution generated lubricadoras washers and objects of study , establishing measures of preventive , corrective and compensatory , which ensure the proper functioning Washing and lubricadoras of the proper application and verification of compliance with environmental regulations , within the field of sustainable development . Based on the environmental assessment and minimization opportunity considered environmentally feasible operating activities and maintenance of the facilities and services of the washing lubricadoras as part of the environmental action plan that will have to take for normal operation.